The Path of Reform: The Consequences of Institutional Volatility. (22nd March 2019) - Bolen, J. Brandon; Williamson, Claudia R.
Summary: The new institutional literature widely acknowledges the benefits of growth‐enhancing institutions but rarely discusses the path of institutional reform. While good institutions stabilize the structure of exchange and decrease uncertainty in market transactions, institutional reform may involve institutional volatility. If institutional volatility increases uncertainty, it can mitigate the benefits of reform. Using a sample of 89 countries from 2000‐2015, this paper empirically examines the effects of institutional volatility on economic growth. We find that institutional volatility decreases economic growth, particularly during liberalization for countries with low quality institutions and low income. In fact, a one standard deviation increase in volatility decreases growth by about 0.50 percentage points. This finding is robust to multiple estimation techniques and omitted variable bias. Evidence is provided suggesting that this effect is partially mediated through volatility's impact on private investment. These results support prior works that policy makers should pursue economic freedom, but our work indicates they should do so along a stable reform path to maximize economic growth.